Getting parents involved in child’s school: using attendance application system based on SMS gateway - Susilowati, Tri; Ihsan Dacholfany, M.; Aminin, Sudirman; Ikhwan, Afiful; Mohd. Nasir, Badlihisham; Huda, Miftachul; Prasetyo, Adi; Maseleno, Andino; Satria, Fiqih; Hartati, Sri; ., Wulandari (International Journal of Engineering and Technology, 2018)
Along with the development of communication technology, and information system, more and more also made the attendance system, and academic information. The development of a more modern absentee system with respect to the honesty side needs to be built as a substitute for manual absence using paper. Attendance system is at once can be a new standard on attendance system in Education environment. The choice of fingerprint attendance system based on communication technology in the form of SMS is because it is more practical, cheap, and efficient to convey information. Parents do not have to bother anymore come to school just to know the presence or absence of his son / daughter. In the implementation of this application, in the early stages of the user must register their identity by using the application program absenteeism built with PHP programming language, to further stored the absence data into the database My SQL which has integrated SMS Gateway through the SMS sending software that is Gammu. In addition with SMS Gateway technology, parents will be easier to obtain information on the presence of his son / daughter. From the student side, it is hoped that it will foster discipline attitude in time because indirectly this application will grow the mental attitude on time to the students, and it is expected that this application can fix any deficiencies in attendance application that has been implemented earlier.Â